First trimester maternal serum PAPP-A and free β-hCG levels and risk of SGA or LGA in women with and without GDM - Tiina Kantomaa; Marja Vääräsmäki; Mika Gissler; Markku Ryynänen; Jaana Nevalainen (BMC, 2024)
Abstract Background Maternal gestational diabetes (GDM), small (SGA) and large (LGA) for gestational age neonates are associated with increased morbidity in both mother and child. We studied how different levels of first trimester pregnancy associated plasma protein-A (PAPP-A) and free beta human chorionic gonadotropin (fβ-hCG) were associated with SGA and LGA in GDM pregnancies and controls. Methods Altogether 23 482 women with singleton pregnancies participated in first trimester combined screening and delivered between 2014 and 2018 in Northern Finland and were included in this retrospective case-control study. Women with GDM (n = 4697) and controls without GDM (n = 18 492) were divided into groups below 5th and 10th or above 90th and 95th percentile (pc) PAPP-A and fβ-hCG MoM levels. SGA was defined as a birthweight more than two standard deviations (SD) below and LGA more than two SDs above the sex-specific and gestational age-specific reference mean. Odds ratios were adjusted (aOR) for maternal age, BMI, ethnicity, IVF/ICSI, parity and smoking. Results In pregnancies with GDM the proportion of SGA was 2.6% and LGA 4.5%, compared to 3.3% (p = 0.011) and 1.8% (p < 0.001) in the control group, respectively. In ≤ 5th and ≤ 10th pc PAPP-A groups, aORs for SGA were 2.7 (95% CI 1.5-4.7) and 2.2 (95% CI 1.4-3.5) in the GDM group and 3.8 (95% CI 3.0-4.9) and 2.8 (95% CI 2.3-3.5) in the reference group, respectively. When considering LGA, there was no difference in aORs in any high PAPP-A groups. In the low ≤ 5 percentile fβ-hCG MoM group, aORs for SGA was 2.3 (95% CI 1.8-3.1) in the control group. In fβ-hCG groups with GDM there was no association with SGA and the only significant difference was ≥ 90 percentile group, aOR 1.6 (95% CI 1.1-2.5) for LGA. Conclusion Association with low PAPP-A and SGA seems to be present despite GDM status. High PAPP-A levels are not associated with increased LGA risk in women with or without GDM. Low fβ-hCG levels are associated with SGA only in non-GDM pregnancies.